Qowa'idul Fiqi'ah: Implementation of Qowaid Fiqhiyah in Answering Contemporary Problems - Muhammad Rahim Harahap (AT-TAFAHUM: Journal of Law, 2025)
This study examines the implementation of Islamic jurisprudence (qowaid) in addressing various contemporary problems emerging in modern society. As general principles in Islamic law, qowaid plays a crucial role in providing solutions to emerging issues not specifically addressed in the Qur'an and Hadith. The purpose of this study is to analyze the relevance and application of Islamic jurisprudence (qowaid) in addressing contemporary issues in the social, economic, technological, health, and modern muamalah (transactions). The research method used is qualitative research with a normative approach and library research. Data sources were obtained from fiqh books, qowaid books, scientific journals, and relevant Islamic legal literature. The analysis was conducted by examining several key principles, such as al-umuru bi maqashidiha (all matters depend on the goal), al-dhararu yuzal (harm must be eliminated), and al-masyaqqatu tajlibu al-taisir (difficulty brings about ease) in the context of contemporary issues. The research results show that the Islamic jurisprudence (qowaid) is of high quality and relevance in addressing the challenges of the times. The principles of Islamic jurisprudence can serve as the basis for ijtihad in establishing laws regarding various modern phenomena, such as digital transactions, the use of information technology, Islamic financial services, and even health and social issues. Thus, the application of Islamic jurisprudence (qowaid) not only maintains the existence of Islamic law but also demonstrates that Islamic law is dynamic, adaptive, and capable of providing benefits to human life in every era.